Análise paramétrica de estruturas multicamadas aplicada a células fotovoltaicas plasmônicas - SOUSA, Miquéias Cruz de (2018)
In this work it is presented a parametric analysis of a multilayer structure composed of three layers: Si02, GaAs – AlGaAs and Au (whose structure is wrapped through the air). In the mathematical model Maxwell equations are used for the calculation of the generalized reflection coefficient magnitude for perpendicular and parallel polarization (represented by |R’m+1+| e |R’m+1|||, respectively) and the Lorentz-Drude model for representing the physical characteristics of the metal constituting the gold layer. For the problem in consideration, we use the mathematical model for the implementation of its programming using Matlab technical computing software. Thus, primarily, it is investigated the behavior |R’M+1+| (|R’m+1+| for m=M) for a frequency range from 100THz to 1000THz, by varying the thickness of each layer of the multilayer structure proposed. In order to complement the exploitation of the results obtained in the initial analysis of |R’M+1+|, the study of the perpendicular electric field magnitude is added to the plane of incidence of the plane wave (|Ezm|, inherent to horizontal or perpendicular polarization) varying along the multilayer structure. However in a second moment, the work proposes an investigation of |R’M+1+| and |R’M+1||| (|R’m+1||| for m=M) as the angle of incidence of the plane wave is modified, also aiming to establish a parallel between the two polarizations. The conclusions regarding |R’M+1+| and |R’M+1||| regarding the variation of the angle of incidence are enhanced with the assessment of the results of |Ezm| and |Eym| (magnitude of the electric field for parallel polarization) in the direction of propagation of the plane wave. In both cases proposed for the study, the results are expressed explaining the best case for each situation evaluated, discussing their respective advantages in relation to others.